The Influence of Gamification on Motivation and Cardiac Variables in Soccer - Lennartz, Rebecca; Stöve, Maike; Talar, Karolina; Kumarampulakkal, Nandu; Dorschky, Eva; Witte, Matthias; Eskofier, Björn (Book of Abstracts of the 29th Annual Congress of the European College of Sport Science, 2024)
INTRODUCTION: Motivation, a complex construct that influences behavior and is a critical factor in an athlete’s success is being extensively researched in sports sciences [1,2]. However, motivation is primarily assessed through motivational questionnaires, which results in a lack of objective, continuous measures during a sports activity. Therefore, this study explores the feasibility of measuring short-term motivation through electrocardiogram (ECG). Gamification elements, aligned with self-determination theory (SDT), fulfilling the three basic needs relatedness, competence, and autonomy were used to influence motivation [3]. METHODS: In this study, 42 healthy soccer players (25 males, 17 females; age: (27,8 ± 7,8) years) performed a soccer drill in a circular space surrounded by a 360° screen. The goal for each player was to score as many goals as possible in two different, randomly ordered, counterbalanced scenarios, each lasting 3 minutes - one incorporating gamification elements aligned with SDT and one without. ECG data (Portabiles, Erlangen, Germany) were recorded during the drill. Postscenario assessments included responses to the Intrinsic Motivation Inventory (IMI) and Player Experience of Needs Satisfaction (PENS), both on a 7-point Likert scale, along with the Borg scale. RESULTS: Six and nine participants, respectively, were excluded from the questionnaires and ECG analyses. The results of the questionnaires, perceived exertion (Borg scale), perceived autonomy, competence and relatedness (PENS), and interest/enjoyment (IMI) showed no significant differences between scenarios. Average heart rate (HR) during the basic scenario was (116, 25 ± 21,76) bpm, while in the gamified version, it was (108, 39 ± 19,13) bpm (p = 0.0322). HR variability (HRV) revealed significantly higher RMSSD (+23 %, p = 0.0139) and SDNN (+17 %, p = 0.0172) values in the gamified version compared to the basic scenario. CONCLUSION: In this work, no effect of the gamification elements on motivation could be measured. Some players reported that they solely paid attention to the task and that they ignored additional elements. Nevertheless, the results showed a lower HR and higher HRV in the gamified scenario compared to the basic one, which indicates lower stress levels [5]. This trend is opposed to previous literature [6]. However, due to the complex and individual character of motivation, future analysis should include a detailed investigation of the physiological responses of individuals as well as a long-term study in the presented set-up. Acknowledgment: This work was supported by VDI/VDE-IT. [1] Clancy R et al. Psychol Sport Exerc., 27: 232-242, 2016. [2] Vallerand R et al. Handbook of sport psychology, 59-83, 2007. [3] Deci E et al. Scand. J. Educ. Res., 38(1): 3-14, 1994. [4] Francisco-Aparicio A et al. New trends in interaction, virtual reality and modeling, 113-126, 2013. [5] Aubert A. et al. Sports Med, 33: 889–919, 2003. [6] Schlömmer M. et al. Sustainability, 13(12), 6608. 2021. <br
Keywords: Cardiac Variables; Gamification; Motivation; Performance; Soccer